Introduction: I am Nothing - Fiol-Matta, Licia (Current Musicology, 2018)
In 1969, at the height of the Cold War, the Puerto Rican singer Lucecita Benítez won the First Festival of Latin Song in the World with her performance of “Génesis”: Cuando nada en la tierra quede que tibie el sol Cuando nadie en la tierra quede que evoque a Dios Cuando sobre la tierra no haya ya ni dolor Solo habrá una lumbre y esa será el amor ¡El amor, el amor! ¡Para empezar! When nothing is left on Earth to feel the warmth of the sun When no one is left on Earth to invoke God When not even pain will be felt on Earth There will only be a flame and that flame will be love Love, Love! To begin again! Considering its lugubrious content, it seems odd, more than forty years later, that the music industry and listening public frantically celebrated “nothingness” in this very melodramatic way. The muscular symphonic orchestra rushed to keep pace with the singer who had appeared, seemingly, out of nowhere and literally came out of the nowhere that was Puerto Rico to Latin America, the United States, and the world. Ironically, the singer’s name means little light, akin to the flame of love that rises after the apocalypse’s destruction in the last, triumphant bars of the song. It is not the name her friends and family use to address her: She is Luz, Luz Esther, or Lucy. Lucecita is a stage name, a diminutive that always has seemed not quite right for this mercurial singer, and yet also on the mark in Latin American Spanish as a signifier for the enormous affection she has evoked in generations of Puerto Ricans. “Lucecita” incorporates the love that the song names as the world’s salvation—resonating with the adoration the singer easily provoked—but it also contains a kernel of societal diminution, mockery, and domestication: women as marginal, minor, and suspect. The song attempted to re-create beginning and end, alpha and omega, genesis and dissolution. It was a response to both the terrifying prospect of global, nuclear annihilation, and the colonial condition of Puerto Rico that diminished social life. It stands as a testament to the increasing paranoia of the small colony, its anguish expressed as an anxiety over its smallness and presumptive incapacity to affect its destiny or the world’s. “Génesis” also entailed a subliminal protest of the topsy-turvy gender and sexual world which the star, paradoxically enough, embodied in her dashing tuxedo and grippingly loud vocal volume. Its author, fellow Puerto Rican Guillermo Venegas Lloveras, found himself suddenly owing his major triumph to a masculine woman, one the public did not know how to read. At the dawn of her career, she was often described as “boyish” or “androgynous.” In 1969, she disconcerted all of Latin America by presenting as mannish. Venegas Lloveras could not have foreseen the artist’s eruption onto the world stage with his song, since she had been a wondrous but inoffensive and “feminine” youth star up until that moment. He probably never imagined that his status as the songwriter of “Génesis” would become subordinate to the performer’s. In a music industry practice that is not yet quite extinct, singers functioned as the placeholders for someone else’s genius. Furthermore, that genius was invariably male, whether the songwriter’s, musician’s, or bandleader’s. Lucecita had transformed Venegas Lloveras’s predictable song into a watershed sonic and visual event. She had single-handedly put Puerto Rico on the map. She was the one the adoring public rushed to see when the winning cohort returned to Puerto Rico. She was the figure that admiring singers and musicians came to respect. It is telling that in his 1992 memoir, Venegas Lloveras wrote, “Total genius is men’s priority. A true man is he who can penetrate everything. Women were born for flirting, not for knowledge; to be dominated, not to dominate; to give children, not ideas. Do you know of a single woman who has attained the status of Thinker? A single woman who has shaken or altered the intellectual conscience of the world? Do you know of a single woman possessing an unparalleled probing capacity [inigualable penetración]?”[1] “Génesis” expressed extreme male melancholy, yet a masculine woman unexpectedly delivered this affect home. The songwriter’s lament for women and men who did not conform to the expected roles of a misogynistic and homophobic society, who dared usurp the masculine domains—music among them—throws into the sharpest of relief just how vexed women’s incursion into pop music can be. [This work is not part of Current Musicology’s Creative Commons license. Copyright, 2016, Duke University Press. All rights reserved. Republished by permission of the copyright holder. www.dukeupress.edu]